Efficient and Ecological Indicators of CI Engine Fuelled with Different Diesel and LPG Mixtures. (2017) - Rimkus, Alfredas; Melaika, Mindaugas; Matijošius, Jonas
Abstract: The effect of additionally fed LPG (Liquefied Petroleum Gas) on the energy and environmental performance of a compression ignition (CI) engine that operates of diesel fuel and the combustion process in it has been examined. In course of the experimental tests, it was found that additionally fed LPG reduced the volume of diesel fuel injected into the cylinder and caused a delay of its injection moment, thus affecting the combustible mixture combustion process and reducing the engine efficiency. Increasing the LPG concentration causes growing of the concentrations of partial combustion products, such as CO (carbon monoxide) and HC (hydrocarbons), in the exhaust gas and the smokiness of the latter; however, emissions of NOx (nitrogen oxides) and CO2 (carbon dioxide) decrease. If 20–60% LPG is added to diesel fuel and the fuel injection advance angle Θ is up to 16 CA (crank angle) bTDC (before the Top Dead Center), the engine efficiency is close to the efficiency of the one operating on diesel fuel, because combustion of the combustible mixture is improved and the concentration of the partial combustion products decreases; however, NOx concentration in the combustion products grows. The analysis of the combustion process upon applying AVL BOOST software showed that increasing the LPG concentration in the mixture of fuels and the injection advance angle Θ causes shortening of combustion duration and the ROHR ( Rate of Heat Release ) becomes more intensive. The latter cause increases mechanical and thermal loads of the engine details.